Leonid Aleksandrovich Shemetkov (Algebra and Discrete Mathematics, 2013)
Ukrainian algebraists with keen sorrow have learned about the death of our colleague, a prominent algebraist and a tremendously efficient science manager of the Republic of Belarus Leonid Aleksandrovich Shemetkov. Leonid A. Shemetkov's entire life was devoted to research and teaching. He was one of the founders of Gomel Algebra School which he had headed for 40 years. For many years, he worked as the President of Francisk Skorina Gomel State University. His excellent achievements were highly praised by his colleagues and the Government: He was elected a Corresponding Member of the National Academy of Sciences of Belarus and he was awarded with the honored title of Distinguished Scientist of Belarus.